2015
DOI: 10.1186/s12866-015-0454-0
|View full text |Cite|
|
Sign up to set email alerts
|

Increased spread and replication efficiency of Listeria monocytogenes in organotypic brain-slices is related to multilocus variable number of tandem repeat analysis (MLVA) complex

Abstract: BackgroundListeria (L.) monocytogenes causes fatal infections in many species including ruminants and humans. In ruminants, rhombencephalitis is the most prevalent form of listeriosis. Using multilocus variable number tandem repeat analysis (MLVA) we recently showed that L. monocytogenes isolates from ruminant rhombencephalitis cases are distributed over three genetic complexes (designated A, B and C). However, the majority of rhombencephalitis strains and virtually all those isolated from cattle cluster in ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…N14-0435 and N11-1515 included as background strains belong to lineage I, serotype 1/2b and lineage II, serotype 1/2a respectively. In addition, L. monocytogenes EGDe a lineage II, serotype 1/2a strain was included in the study as a reference strain and L. innocua J5051 was included as a negative control in some of the experiments (Guldimann et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…N14-0435 and N11-1515 included as background strains belong to lineage I, serotype 1/2b and lineage II, serotype 1/2a respectively. In addition, L. monocytogenes EGDe a lineage II, serotype 1/2a strain was included in the study as a reference strain and L. innocua J5051 was included as a negative control in some of the experiments (Guldimann et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Hypovirulent clones of L. monocytogenes generally belong to lineage II (Jacquet et al, 2004;Maury et al, 2016;McLauchlin, 1990;Orsi et al, 2011), while hypervirulent clones have been predominantly found in lineage I, which is also the most prevalent lineage in animal and human infection (Chenal-Francisque et al, 2011;Jacquet et al, 2004;Kim et al, 2018;Maury et al, 2016;Orsi et al, 2011). Of those, strains belonging to sequence type (ST) 1 are particularly prevalent in CNS infection of ruminants and humans (Dreyer et al, 2016;Maury et al, 2016) and behave hyperinvasive in vitro compared to the reference strain EGD-e and other strains from lineage II (Dreyer et al, 2016;Guldimann et al, 2015;Rupp et al, 2017). Differences in genomic gene content suggest that lineage I strains harbor specific genes that may confer hyperinvasion and hypervirulence resulting in the higher prevalence of these strains in clinical infection (Dreyer et al, 2016;Maury et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for strains from specific sequence types (ST, as determined by multilocus sequence typing (MLST)), namely ST1 and 4. These two ST additionally behave hypervirulent and hyperinvasive in experimental in vivo and in vitro infections (Dreyer et al, ; Guldimann et al, ; Maury et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence in support of this proposition is provided by studies of natural isolates of L. monocytogenes . Human clinical isolates, including epidemic strains, are more likely to exhibit enhanced spread compared to the lab reference strain 10403S and to strains from ruminants or food sources ( 50 , 51 ). The plaque sizes of these hyperspreading isolates are larger by 1.2- to 1.5-fold, which contextualizes the 1.5- to 2-fold increase in spread areas observed in RECON-deficient cells.…”
Section: Discussionmentioning
confidence: 99%